2014
DOI: 10.1016/j.enpol.2014.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Governance of CO2 markets: Lessons from the EU ETS

Abstract: The European emissions trading scheme (EU ETS) is the centrepiece of Europe's climate policy. The system has been undermined variously by the weakness of its regulation, an undesirable overlap with other public policies and the far-reaching economic and financial crisis that caused the market price of allowances to plunge. This article attempts to identify the conditions for making the coming years of the EU ETS a success. It draws historical lessons from the eight years the scheme has been in operation, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 10 publications
(1 reference statement)
1
54
0
1
Order By: Relevance
“…This is because every Member state hopes to protect their own firms and declare too many carbon quotas during the first two phases. This is the main reason of the low price of carbon quota [28]. Moreover, this has led to the different emission benchmark of the same industry in different countries [33].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because every Member state hopes to protect their own firms and declare too many carbon quotas during the first two phases. This is the main reason of the low price of carbon quota [28]. Moreover, this has led to the different emission benchmark of the same industry in different countries [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The carbon emission quotas were predominantly allocated for free in the first two phases. In the third phase, the majority of the quotas are sold by auction [28]. Oestreich and Tsiakas [29] find that there is a large and statistically significant carbon premium in stock returns, which is primarily driven by the free allocation of carbon quotas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sreekanth et al (2014), Erickson et al (2014), Cormier and Bellassen (2012) studied the clean development mechanism as an example of the most significant market based mechanism. Perthuis and Trotignon (2013) studied the EU Emission trading scheme as an example of market based approach. Burtraw (2013), Rabe (2016), Carmton and Stoft (2012), Lutz (2013), Repetto (2013), Anand and Giraud-Carrier (2013) studied only the cap-and-trade markets.…”
Section: Market Based Approachmentioning
confidence: 99%
“…The literature on the EU ETS has been growing very rapidly devoting particular attention to specific aspects or problems encountered by the EU ETS over these years, such as the over-allocation registered in the early phases (Gilbert et al, 2004;Sijm, 2005), the causes, components and consequences of the observed price volatility (Alberola et al, 2008;Chevallier, 2012a;Medina et al, 2014;Gronwald and Hintermann, 2015), the drivers of the price fall in Phase II (Koch et al, 2014), the existence of frauds and monitoring problems (Frunza et al, 2011), the role of banking and borrowing for the functioning of the scheme (Caton et al, 2015;Chevallier, 2012b), the possible carbon leakage effects induced by the EU ETS (Clò, 2010: Martin et al, 2014a, its estimated impact on emissions abatement (Germà and Stephan, 2015), the structural measures proposed by the European Commission to reform the EU ETS (Clò et al, 2013;de Perthuis and Trotignon, 2014), the perspective of linking the EU ETS with other similar ETSs around the world (Anger, 2008;Tuerk et al, 2009;Ranson and Stavins, 2015). Much of the literature, moreover, has focused on the effects of the EU ETS on technological innovation, using surveys of managerial interviews and/or performing estimations of econometric models that account for the EU ETS among their covariates to test whether the implementation of the system has spurred environmental-friendly innovations (see Abrell et al, 2011;Aghion et al, 2009;Anderson and Di Maria, 2011;Borghesi et al, 2015;Calel and Dechezleprêtre, 2015;Hoffman, 2007;Martin et al, 2011;Rogge et al, 2011;Schmidt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%